Environmental Pollution and Health in Chilean Older Adults: Impact on Quality of Life and Functional Autonomy - Jofre-Saldia, E (John Wiley and Sons Inc, 2024)
Background and Aims: Due to increased urbanization and industry, environmental pollution is a serious public health concern. Globally, the quality of life is particularly lowered by exposure to high amounts of particulate matter (PM). Chile has five industrial zones with high pollution levels, called “sacrifice zones.” However, the effect of polluted air on the quality of life and functional autonomy (FA) of older people living in industrial zones with high pollution levels is unknown. Therefore, this study aimed to determine the quality of life and FA differences between Chilean older women (OW) living in areas with lower and higher PM levels. Materials and Methods: Seventy-two OW volunteered for this study. The sample was divided into Zone 1 (PM2.5 ≤ 15 µg/m3, n = 36) and Zone 2 (PM2.5 > 15 µg/m3, n = 36). The variables were quality of life—assessed through the SF-36v2.0 questionnaire, and FA—assessed through the GDLAM protocols. Differences between zones were tested by Student s t-test and Mann–Whitney test, both for independent samples (p < 0.05). Results: All eight dimensions of quality of life were lower in Zone 2, of which the role emotional (RE) showed significant differences between zones (p < 0.05). Performance on the GDLAM protocols and the FA index were lower in Zone 2 (p ˃ 0.05). Conclusion: OW in Zone 2 showed lower quality of life and FA. PM could affect the older population s physical and mental health and, therefore, the quality of life. © 2024 The Authors. Health Science Reports published by Wiley Periodicals LLC.